PENGARUH NIKOTIN TERHADAP JUMLAH SEL LEYDIG PADA MENCIT (Musmusculus) - Iis Rahmawati (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2013)
Nicotine which is one of toxic component in cigarette smoke had been reported to inhibit androgen biosynthesis and Leydig cell growth. Cigarette smoking alters plasma testosterone concentrations inmen. The effect of cigarette smoke can spoil sperm viability and spermatogenesis. It can cause hormonal condition and trigger the emergence of toxic substance on sperm that it can harm male fertility.The research design employed in this study was Post Test Only Control Group Design. The samples were adult male musmusculus. There were six groups of research subject chosen randomly after homogenization. Three groups were the control group and the other three were the experimental group. The subjects in the experimental group were injected with nicotine subcutaneously for one week, two weeks and three week with the same dosage namely 5 mg/kg bodyweight/day. The final observation was aimed at calculating the number of Leydig cell. The result of the one way Anova showed that the cell Leydig had a statistically significant difference on some experimental groups (p < 0.05). LSD test showed that there was significant difference between Leydig cells of P3 and K3; P2 and K3; P1 and K3. The conclusion of this research was that nicotine caused a decrease in the number of Leydig cell.